Antibiotic prophylaxis in laparoscopic cholecystectomy: a randomized controlled trial. - Yoichi Matsui; Sohei Satoi; Masaki Kaibori; Hideyoshi Toyokawa; Hiroaki Yanagimoto; Kosuke Matsui; Morihiko Ishizaki; A-Hon Kwon (PLoS ONE)
Background Recent meta-analyses concluded that antibiotic prophylaxis is not warranted in low-risk laparoscopic cholecystectomy. However, most trials in the meta-analyses had a relatively small sample size and were statistically underpowered. In addition, many of the trials mentioned potential cost savings owing to the elimination of prophylactic antibiotics. However, no trial has statistically estimated the cost effectiveness. To evaluate the results of meta-analyses, we conducted a randomized controlled trial on the role of prophylactic antibiotics in low-risk laparoscopic cholecystectomy with an adequate sample size. Methods From March 2007 to May 2013, at the Department of Surgery, Kansai Medical University, patients who were scheduled for elective laparoscopic cholecystectomy were randomly assigned to one of two arms: those who were and were not administered prophylactic antibiotics. The primary endpoint was the occurrence of postoperative infections and secondary endpoints were postoperative hospital stay and medical costs. Findings During the study period, 518 patients were assigned to the Antibiotics group and 519 to the No antibiotics group. Occurrences of surgical site infections, distant infections and overall infections were significantly lower in the Antibiotics group than in the No antibiotics group (0.8 vs. 3.7%, p = 0.001, OR: 0.205 (95%CI: 0.069 to 0.606); 0.4 vs. 3.1%, p = 0.0004, OR: 0.122 (95%CI: 0.028 to 0.533); 1.2 vs. 6.7%; p<0.0001, OR: 0.162 (95%CI: 0.068 to 0.389), respectively). The postoperative hospital stay was significantly shorter in the Antibiotics group (mean, SD: 3.69±1.56 vs. 4.07±3.00; p = 0.01) and the postoperative medical costs were significantly lower in the Antibiotics group (mean, SD: $766±341 vs. 832±670; p = 0.047). Multivariable analysis showed that independent risk factors for postoperative infectious complications were no prophylactic antibiotics (p<0.0001) and age 65 or older (p = 0.006). Conclusions Perioperative administration of prophylactic antibiotics should be recommended in laparoscopic cholecystectomy to prevent postoperative infectious complications and to reduce medical costs. Trial registration UMIN Clinical Trials Registry UMIN000003749.